Nano zirconium hydroxide, preparation method and application thereof, and n-butane skeletal isomerization catalysis method

Spherical and/or spherical nanozirconium hydroxide was successfully prepared by mixing the template agent with the alkaline solution and zirconium saline aqueous solution, which solved the problem of nanozirconium hydroxide preparation in the prior art and improved its catalytic performance.

CN119706926AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311226545.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-28
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

The prior art has failed to effectively prepare nanoscale zirconium hydroxide and its regular morphology, and its catalytic properties are greatly affected by particle size and morphology.

Method used

By mixing the template agent with an alkaline solution, adding zirconium brine solution to form a precipitate and undergoing a hydrothermal reaction, finally cooling and drying to obtain spherical and/or spherical nanozirconium hydroxide.

Benefits of technology

The prepared nanozirconium hydroxide has a particle size distribution of 10-30 nm and is suitable as a catalyst support, improving the single-way conversion of n-butane and isobutane selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706926A_ABST
    Figure CN119706926A_ABST
Patent Text Reader

Abstract

The invention relates to nano zirconium hydroxide, a preparation method thereof and an n-butane skeletal isomerization catalysis method using the nano zirconium hydroxide. The nano zirconium hydroxide has a spherical and / or sphere-like morphology, and the particle size distribution is 10-30nm. The nano zirconium hydroxide is especially suitable for being used as a catalyst carrier, is especially suitable for being used as a carrier of an n-butane isomerization catalyst, and can improve the conversion per pass of n-butane and the selectivity of isobutane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to nano zirconium hydroxide and a preparation method thereof and a catalytic method for applying normal butane skeleton isomerization. Background Art

[0002] Zirconium hydroxide is a water-insoluble, slightly alkaline amphoteric hydroxide. It is non-toxic and tasteless, insoluble or slightly soluble in water, insoluble in alcohol, alkali and ammonium salt solutions, easily soluble in inorganic acids such as hydrochloric acid, and decomposes into zirconium dioxide and water at 500°C. Due to its amphoteric properties, it can react with acids and alkalis, and when melted, it reacts with strong alkalis to form crystalline orthozirconate. The zirconium hydroxide first obtained by the reaction of zirconium salt aqueous solution with caustic soda (or ammonia) aqueous solution is called α-type zirconic acid, which is soluble in dilute acid. The one that precipitates under heating conditions is called β-type zirconic acid, which is difficult to dissolve in water and acid.

[0003] Zirconium hydroxide is used to make other zirconium compounds, pigments, dyes, glass, etc. It is mainly used to prepare zirconium and zirconium compounds, and is also used as fillers, catalysts, deodorants and pigments in industries such as plastics, rubber, and ion exchange resins. It is used as an analytical reagent, and is also used in the preparation of chromium compounds and the preparation of pigments; it is used as an intermediate for other zirconium products.

[0004] CN111422904A discloses a method for producing zirconium hydroxide, which comprises adding a zirconium oxychloride solution and an alkaline solution into a reaction tank simultaneously to generate a zirconium hydroxide precipitate.

[0005] CN107500351A describes the preparation of zirconium hydroxide by bubbling ammonia into a zirconium solution.

[0006] However, the production methods described in these technologies do not disclose how to prepare nano-scale zirconium hydroxide and nano-zirconium hydroxide with regular morphology. The prior art also rarely mentions how to prepare nano-scale zirconium hydroxide, and most of them are about how to prepare nano-zirconium oxide. For example, CN101913649B describes the preparation of nano-zirconium oxide by adding a template and hydrothermally preparing at 115°C to 160°C. This method directly obtains crystalline zirconium oxide from the solution at a high temperature of 115°C to 160°C, but cannot obtain amorphous zirconium hydroxide. CN101049965A describes the use of oxalic acid as a precipitant to obtain a zirconium oxalate precursor precipitate, which is then calcined and decomposed at 600°C to obtain nano-zirconium oxide with an average particle size distribution of 10 to 30nm. This method also does not go through a zirconium hydroxide intermediate.

[0007] The catalytic performance of zirconium hydroxide is affected by the atomic arrangement and the number of unsaturated bonds on its surface. The particle size and morphology of zirconium hydroxide greatly affect the atomic arrangement and the number of unsaturated bonds on its surface, which will affect the catalytic performance of zirconium hydroxide and the preparation of other catalysts based on zirconium hydroxide, such as solid superacid SO4. 2-—ZrO2. Preparation of active SO4 2- One of the important conditions for ZrO2 solid superacid is generally considered to be that amorphous hydrated zirconium oxide should be treated with a liquid sulfating agent; sulfation of zirconium oxide crystals is ineffective. Summary of the invention

[0008] The purpose of the present invention is to provide a nano zirconium hydroxide and a preparation method thereof and a catalytic method for the skeletal isomerization of n-butane. The nano zirconium hydroxide of the present invention has a spherical and / or spherical-like morphology and is suitable for use as a catalyst carrier.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a nano zirconium hydroxide having a spherical and / or quasi-spherical morphology and a particle size distribution of 10-30 nm.

[0010] The second aspect of the present invention provides a method for preparing the nano zirconium hydroxide of the present invention, the method comprising:

[0011] (1) mixing a template with an alkaline solution; the template comprises a benzenesulfonic acid compound;

[0012] (2) mixing the solution obtained in step (1) with an aqueous zirconium salt solution to generate a precipitate;

[0013] (3) subjecting the product obtained in step (2) to a hydrothermal reaction;

[0014] (4) Cooling the product obtained in step (3), separating to obtain a solid, and drying to obtain spherical and / or quasi-spherical nano zirconium hydroxide.

[0015] The third aspect of the present invention provides an application of the nano zirconium hydroxide described in the present invention in a catalyst carrier.

[0016] A fourth aspect of the present invention provides a catalytic method for skeletal isomerization of n-butane, the catalytic method comprising: contacting a gas containing n-butane with a catalyst and H2, wherein the catalyst contains the nano zirconium hydroxide described in the present invention.

[0017] Through the above technical solution, the present invention provides nano zirconium hydroxide having a spherical and / or quasi-spherical morphology and a particle size distribution of 10-30 nm; in a preferred embodiment of the present invention, the nano zirconium hydroxide has a narrow particle size distribution.

[0018] The preparation method of nano zirconium hydroxide of the present invention has the advantages of simple process and easy operation and control.

[0019] The nano zirconium hydroxide of the present invention is particularly suitable as a catalyst carrier, and is particularly suitable as a carrier of an isomerization catalyst, and can improve the single-pass conversion rate of normal butane and the selectivity of isobutane. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a scanning electron microscope (SEM) image of the nano zirconium hydroxide prepared in Example 1;

[0021] Figure 2 is a transmission electron microscope (TEM) image of the nano zirconium hydroxide prepared in Example 1;

[0022] Figure 3 is a scanning electron microscope (SEM) image of the zirconium hydroxide prepared in Comparative Example 1;

[0023] Figure 4 This is a scanning electron microscope (SEM) image of the nano zirconium hydroxide prepared in Comparative Example 2. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The first aspect of the present invention provides a nano zirconium hydroxide having a spherical and / or quasi-spherical morphology and a particle size distribution of 10-30 nm.

[0026] The nano zirconium hydroxide has a narrow particle size distribution. According to a preferred embodiment of the present invention, more than 85% of the nano zirconium hydroxide has a particle size distribution of 15-25 nm.

[0027] In the present invention, the specific surface area of ​​the nano zirconium hydroxide can be selected in a wide range. According to a preferred embodiment of the present invention, the specific surface area of ​​the nano zirconium hydroxide is 350-390m 2 / g.

[0028] In the present invention, the total pore volume of the nano zirconium hydroxide can be selected in a wide range. According to a preferred embodiment of the present invention, the total pore volume of the nano zirconium hydroxide is 0.42-0.72 cm 3 / g.

[0029] In the present invention, the average pore size of the nano zirconium hydroxide can be selected in a wide range. According to a preferred embodiment of the present invention, the average pore size of the nano zirconium hydroxide is 5.4-8.2 nm.

[0030] Nano zirconium hydroxides having the aforementioned properties can achieve the purpose of the present invention. The present invention has no special requirements for the preparation method of the catalytic oxidation catalyst. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the nano zirconium hydroxide of the present invention, the method comprising: the preparation method of the nano zirconium hydroxide, the method comprising:

[0031] (1) mixing a template with an alkaline solution; the template comprises a benzenesulfonic acid compound;

[0032] (2) mixing the solution obtained in step (1) with an aqueous zirconium salt solution to generate a precipitate;

[0033] (3) subjecting the product obtained in step (2) to a hydrothermal reaction;

[0034] (4) Cooling the product obtained in step (3), separating to obtain a solid, and drying to obtain spherical and / or quasi-spherical nano zirconium hydroxide. The preparation method of nano zirconium hydroxide of the present invention has the advantages of simple process and easy operation and control.

[0035] In the present invention, the benzenesulfonic acid compound can be selected from a wide range. According to a preferred embodiment of the present invention, the benzenesulfonic acid compound is selected from one of the compounds shown in formula (I);

[0036]

[0037] Wherein, R1, R2, and R3 are each independently selected from hydrogen, amino, hydroxyl, or C1-C12 alkyl;

[0038] X is selected from one of H, Na or NH4.

[0039] According to a preferred embodiment of the present invention, in formula (I), R1 and R3 are hydrogen; and R2 is at least one selected from hydrogen, amino, hydroxyl, methyl, ethyl and dodecyl.

[0040] According to a preferred embodiment of the present invention, the benzenesulfonic acid compound is selected from at least two of p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and 4-hydroxybenzenesulfonic acid, preferably a mixture of p-toluenesulfonic acid and dodecylbenzenesulfonic acid, and more preferably the molar ratio of toluenesulfonic acid to dodecylbenzenesulfonic acid is 0.5-2: 1. Thus, the activity and selectivity of the carrier as a catalyst, especially the activity and selectivity of the isomerization catalyst, can be achieved.

[0041] In the present invention, in step (2), the ratio of the amount of the alkaline substance to the zirconium salt can be selected in a wide range. According to a preferred embodiment of the present invention, the alkaline substance is OH - zirconium salts are calculated as zirconium, OH - :Zr=2:1-4.6:1.

[0042] In the present invention, in step (2), the optional range of the usage ratio of the template agent to the zirconium salt is relatively wide. According to a preferred embodiment of the present invention, in terms of molar ratio, the template agent: Zr = 3-40:100.

[0043] In the present invention, in step (2), the zirconium salt solution may have a wide concentration range. According to a preferred embodiment of the present invention, the concentration of the zirconium salt in the zirconium salt solution is 10-50 wt%.

[0044] In the present invention, in step (2), the mixing temperature can be selected in a wide concentration range. According to a preferred embodiment of the present invention, the mixing temperature is 35-60°C.

[0045] In the present invention, in step (3), the hydrothermal reaction conditions may be selected in a wide range. According to a preferred embodiment of the present invention, the hydrothermal conditions include: a temperature of 90°C to 115°C, preferably 95°C to 115°C; and / or a time of 8 to 72 hours.

[0046] According to a preferred embodiment of the present invention, in step (4), the product obtained in step (3) is cooled to below 35°C.

[0047] In the present invention, in step (4), there is no particular limitation on the drying conditions, and conventional drying conditions in the art can achieve the purpose of the present invention. The following exemplary description is provided, but the scope of the present invention is not limited thereto. According to one embodiment of the present invention, the drying conditions include: a drying temperature of 110-120°C; and a drying time that can be determined according to actual needs, preferably a drying time of 12-24h.

[0048] In the present invention, in step (1), the alkaline substance may be selected from a wide range of substances, which are described below for exemplary purposes but are not intended to limit the scope of the present invention. According to one embodiment of the present invention, the alkaline substance is selected from at least one of aqueous ammonia, sodium hydroxide, sodium carbonate and ammonium carbonate, preferably aqueous ammonia.

[0049] In the present invention, in step (2), there are many types of zirconium salts to choose from. According to a preferred embodiment of the present invention, the zirconium salt is selected from zirconium oxychloride and / or zirconium nitrate.

[0050] According to a preferred embodiment of the present invention, in step (2), the solution obtained in step (1) is dripped into the zirconium salt aqueous solution at a constant flow rate, preferably at a flow rate of 10-100 mL / min.

[0051] According to a preferred embodiment of the present invention, in step (3), a hydrothermal reaction is carried out under constant temperature conditions.

[0052] According to a preferred embodiment of the present invention, the method for preparing nano zirconium hydroxide comprises:

[0053] (1) mixing a benzenesulfonic acid compound template with aqueous ammonia;

[0054] (2) dropping the solution obtained in step (1) into an aqueous zirconium salt solution at a constant flow rate to generate a precipitate;

[0055] (3) subjecting the product obtained in step (2) to a hydrothermal reaction; the hydrothermal conditions include: a temperature of 90° C. to 115° C.; and a time of 8 to 72 hours;

[0056] (4) Cooling and centrifuging the product obtained in step (3) to obtain a solid, and drying at 110° C. to 120° C. to obtain spherical and / or quasi-spherical nano zirconium hydroxide.

[0057] The third aspect of the present invention provides an application of the nano zirconium hydroxide of the present invention in a catalyst carrier, preferably in the preparation of an isomerization catalyst. The nano zirconium hydroxide of the present invention is particularly suitable as a catalyst carrier, especially suitable as a carrier of an n-butane isomerization catalyst, which can improve the n-butane single-pass conversion rate and isobutane selectivity.

[0058] The fourth aspect of the present invention provides a catalytic method for skeletal isomerization of n-butane, the method comprising: contacting a raw material containing n-butane with a catalyst and H2, the catalyst comprising the nano zirconium hydroxide of the present invention. The nano zirconium hydroxide of the present invention is particularly suitable as a catalyst carrier, and is used as a carrier of a n-butane isomerization catalyst, which can improve the single-pass conversion rate of n-butane and the selectivity of isobutane.

[0059] In the present invention, there is no particular limitation on the type of the catalyst, and it may be a conventional catalyst active component in the art. Preferably, the catalyst active component is copper oxide and / or aluminum oxide.

[0060] According to a preferred embodiment of the present invention, in the catalyst, the molar ratio of elements is Al:Cu:Zr=(0.4-7):(0.4-7):100.

[0061] In the present invention, the catalyst preparation method comprises: impregnating aluminum salt and / or copper salt on the nano zirconium hydroxide of the present invention, and then drying and calcining.

[0062] In the present invention, there is no particular limitation on the contact conditions, which may be conventional n-butane skeletal isomerization catalytic conditions in the art. According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 180-220° C.; and a pressure of 0.5-1.5 MPa.

[0063] According to a preferred embodiment of the present invention, the molar ratio of hydrogen to hydrocarbon is 0.1-1.

[0064] According to a preferred embodiment of the present invention, the volume space velocity of n-butane is 0.2-2h -1 .

[0065] The present invention will be described in detail below by way of examples, but these examples do not limit the scope of the present invention in any way.

[0066] In the following examples, the specific surface area, average pore diameter and pore volume were measured by using a Tristar 3000 specific surface analyzer produced by Micrometrics.

[0067] The testing method of nano zirconium hydroxide particle size is based on the obtained electron microscope image and calculated according to the TEM image.

[0068] Example 1

[0069] (1) adding 17.2 g of p-toluenesulfonic acid into 612 g of 10 wt% ammonia water, stirring and dissolving, to obtain an alkaline solution;

[0070] (2) adding 322.2 g of zirconium oxychloride octahydrate into 1000 mL of deionized water, stirring to dissolve to obtain a zirconium solution, and adding the prepared alkaline solution dropwise (at a dropping speed of 20 mL / min) into the zirconium solution at 50° C., stirring at a stirring speed of 300 rpm;

[0071] (3) After all the addition is completed, continue stirring for 1 hour, then transfer to a crystallization kettle, heat to 100°C, and keep at a constant temperature for 24 hours;

[0072] (4) The product obtained in step (3) was cooled to room temperature, filtered, washed with water, and the obtained solid was placed in an oven at 120° C. and dried for 24 hours; the resulting carrier zirconium hydroxide was numbered ZH-1, and the SEM image was shown in FIG. Figure 1 , TEM image see Figure 2 , BET characterization data are shown in Table 1.

[0073] The zirconium hydroxide has a spherical and / or quasi-spherical morphology, and a particle size of 10-30 nm, of which 87% is distributed in the range of 15-25 nm, and the remaining 13% is distributed in the range of ≥10 nm and <15 nm and >25 and ≤30 nm.

[0074] Example 2

[0075] (1) adding 23.2 g of 4-hydroxybenzenesulfonic acid into 300 g of a 20 wt % sodium hydroxide aqueous solution, stirring and dissolving to obtain an alkaline solution;

[0076] (2) 143.1 g of zirconium nitrate pentahydrate was added to 966 mL of deionized water and stirred to dissolve to obtain a zirconium solution. The prepared alkaline solution was added dropwise (at a dropping speed of 100 mL / min) to the zirconium solution at 35° C. while stirring at a stirring speed of 300 rpm.

[0077] (3) After all the addition is completed, continue stirring for 1 hour, then transfer to a crystallization kettle, heat to 95°C, and keep at a constant temperature for 72 hours;

[0078] (4) The product obtained in step (3) was cooled to room temperature, filtered, washed with water, and the obtained solid was placed in an oven at 110° C. and dried for 24 hours; the finally obtained carrier zirconium hydroxide was numbered ZH-2, and the SEM and TEM characterization results were similar to those of ZH-1. The BET characterization data are shown in Table 1.

[0079] The zirconium hydroxide has a spherical and / or quasi-spherical morphology, and a particle size of 10-30 nm, of which 87% is distributed in the range of 15-25 nm, and the remaining 13% is distributed in the range of ≥10 nm and <15 nm and >25 and ≤30 nm.

[0080] Example 3

[0081] (1) adding 10.3 g of ammonium dodecylbenzene sulfonate to 533 g of 10 wt % ammonia water, stirring to dissolve, and then adding 19.2 g of ammonium carbonate to the solution, stirring to dissolve, to obtain an alkaline solution;

[0082] (2) 322.2 g of zirconium oxychloride octahydrate was added to 322.2 mL of deionized water, and the solution was dissolved by stirring to obtain a zirconium solution. At 60° C., the prepared alkaline solution was added dropwise (at a dropping speed of 10 mL / min) to the zirconium solution while stirring at a stirring speed of 300 rpm;

[0083] (3) After all the addition is completed, continue stirring for 1 hour, then transfer to a crystallization kettle, heat to 115°C, and keep at a constant temperature for 8 hours;

[0084] (4) The product obtained in step (3) was cooled to room temperature, filtered, washed with water, and the obtained solid was placed in an oven at 120° C. and dried for 24 hours; the finally obtained carrier zirconium hydroxide was numbered ZH-3, and the SEM and TEM characterization results were similar to those of ZH-1. The BET characterization data are shown in Table 1.

[0085] The zirconium hydroxide has a spherical and / or quasi-spherical morphology, and a particle size of 10-30 nm, of which 85% is distributed in the range of 15-25 nm, and the remaining 15% is distributed in the range of ≥10 nm and <15 nm and >25 and ≤30 nm.

[0086] Example 4

[0087] (1) adding 34.8 g of sodium dodecylbenzene sulfonate to 612 g of 10 wt % ammonia water, stirring and dissolving, to obtain an alkaline solution;

[0088] (2) adding 322.2 g of zirconium oxychloride octahydrate into 1000 mL of deionized water, stirring to dissolve to obtain a zirconium solution, and adding the prepared alkaline solution dropwise (at a dropping speed of 30 mL / min) into the zirconium solution at 50° C., stirring at a stirring speed of 300 rpm;

[0089] (3) After all the addition is completed, continue stirring for 1 hour, then transfer to a crystallization kettle, heat to 110°C, and keep at a constant temperature for 24 hours;

[0090] (4) The product obtained in step (3) was cooled to room temperature, filtered, washed with water, and the obtained solid was placed in an oven at 120° C. and dried for 24 hours; the finally obtained carrier zirconium hydroxide was numbered ZH-4, and the SEM and TEM characterization results were similar to those of ZH-1. The BET characterization data are shown in Table 1.

[0091] The zirconium hydroxide has a spherical and / or quasi-spherical morphology and a particle size of 10 to 30 nm, of which 86% is distributed in the range of 15 to 25 nm, and the remaining 14% is distributed in the range of ≥10 nm and <15 nm and >25 and ≤30 nm.

[0092] Example 5

[0093] The method of Example 1 is followed, except that the template is a mixture of 8.6 g p-toluenesulfonic acid and 16.3 g dodecylbenzenesulfonic acid; the other conditions are the same as Example 1. The zirconium hydroxide has a spherical and / or quasi-spherical morphology and a particle size of 10 to 30 nm. The BET characterization data is shown in Table 1.

[0094] Example 6

[0095] The method of Example 1 is followed, except that the hydrothermal constant temperature in step (3) is 90° C.; the other conditions are the same as those of Example 1. The zirconium hydroxide has a spherical and / or quasi-spherical morphology and a particle size of 10 to 30 nm. The BET characterization data are shown in Table 1.

[0096] Example 7

[0097] The method of Example 1 is different in that the template is p-aminobenzenesulfonic acid; the other conditions are the same as Example 1. The zirconium hydroxide has a spherical and / or quasi-spherical morphology and a particle size of 10 to 30 nm. The BET characterization data is shown in Table 1.

[0098] Comparative Example 1

[0099] The method of Example 1 is followed, except that in step (1), no p-toluenesulfonic acid template is added when preparing the alkaline solution; the remaining conditions are the same as in Example 1. The zirconium hydroxide finally obtained is numbered ZH-A, and the SEM image is shown in Figure 3 The zirconium hydroxide has an irregular morphology and is a large mass of particles; the BET characterization data are shown in Table 1.

[0100] Comparative Example 2

[0101] The method of Example 1 is followed, except that p-toluenesulfonic acid is added to the zirconium oxychloride aqueous solution in step (2) instead of the ammonia water in step (1); specifically as follows:

[0102] (1) measuring 612 g of 10 wt % ammonia water as an alkaline solution;

[0103] (2) 17.2 g of p-toluenesulfonic acid and 322.2 g of zirconium oxychloride octahydrate were added to 1000 mL of deionized water and stirred to dissolve to obtain a zirconium solution. At 50° C., the prepared alkaline solution was added dropwise (at a dropping speed of 20 mL / min) to the zirconium solution while stirring at a stirring speed of 300 rpm;

[0104] (3) After all the addition is completed, continue stirring for 1 hour, then transfer to a crystallization kettle, heat to 100°C, and keep at a constant temperature for 24 hours;

[0105] (4) The product obtained in step (3) was cooled to room temperature, filtered, washed with water, and the obtained solid was placed in an oven at 120° C. and dried for 24 hours; the resulting zirconium hydroxide was numbered ZH-B, and the SEM image was shown in FIG. Figure 4 The zirconium hydroxide has an irregular morphology and is a large mass of particles; the BET characterization data are shown in Table 1.

[0106] Table 1

[0107]

[0108] Embodiment 8-14

[0109] The zirconium hydroxide prepared in Examples 1-7 was used as a carrier to prepare a catalyst for catalyzing the isomerization of n-butane.

[0110] Catalyst preparation: 6.3g aluminum sulfate 18hydrate and 4.7g copper sulfate pentahydrate are placed in a beaker and dissolved with appropriate amount of water. The prepared aqueous solution is added dropwise to 50g zirconium hydroxide while stirring (initial wet impregnation method). After all the addition is completed, continue stirring for a period of time to make it evenly mixed. After standing at room temperature for 24 hours, put it in a 130℃ oven to dry for 24 hours, and finally place it in a muffle furnace at 600℃ for 4 hours to obtain a n-butane isomerization catalyst.

[0111] Catalyst evaluation method: The performance evaluation of the n-butane skeletal isomerization catalyst was carried out on a fixed bed reactor. The reaction tube specification was 5mm×40cm, the catalyst loading was 5mL, the particle size was 20-40 mesh, and it was placed in the constant temperature zone of the furnace. The reaction temperature was 200℃, the hydrogen pressure was 1MPa, and the butane volume space velocity was 1h -1 , the hydrogen-to-hydrocarbon molar ratio is 1:1. The catalyst needs to be activated before use. The catalyst is activated by heating in a nitrogen flow containing 10% volume fraction of hydrogen. The activation temperature is 350°C and the activation time is 8 hours. The catalyst performance evaluation results are shown in Table 2.

[0112] Comparative Examples 3-4

[0113] The method of Example 8 was followed, except that the catalysts were prepared using zirconium hydroxide prepared in Comparative Examples 1-2, respectively, and the other conditions were the same as in Example 8. The catalyst performance evaluation results are shown in Table 2.

[0114] Table 2

[0115]

[0116]

[0117] It can be seen from the results in Table 2 that the n-butane isomerization catalyst using the zirconium hydroxide prepared by the present invention as a carrier has better activity.

[0118] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A nano zirconium hydroxide, characterized in that: The nano zirconium hydroxide has a spherical and / or quasi-spherical morphology, and a particle size distribution of 10-30 nm.

2. The nanozirconium hydroxide according to claim 1, wherein More than 85% of the nano zirconium hydroxide has a particle size distribution of 15-25 nm.

3. The nano zirconium hydroxide according to claim 1 or 2, wherein: The specific surface area of ​​the nano zirconium hydroxide is 350-390m 2 / g; and / or The total pore volume of the nano zirconium hydroxide is 0.42-0.72 cm 3 / g; and / or The average pore size of the nano zirconium hydroxide is 5.4-8.2 nm.

4. A method for preparing nano zirconium hydroxide according to any one of claims 1 to 3, characterized in that: The method includes: (1) mixing a template with an alkaline solution; the template comprises a benzenesulfonic acid compound; (2) mixing the solution obtained in step (1) with an aqueous zirconium salt solution to generate a precipitate; (3) subjecting the product obtained in step (2) to a hydrothermal reaction; (4) Cooling the product obtained in step (3), separating to obtain a solid, and drying to obtain spherical and / or quasi-spherical nano zirconium hydroxide.

5. The preparation method according to claim 4, wherein: The benzenesulfonic acid compound is selected from one of the compounds shown in formula (I); Wherein, R1, R2, and R3 are each independently selected from hydrogen, amino, hydroxyl, or C1-C12 alkyl; X is selected from one of H, Na or NH4.

6. The preparation method according to claim 5, wherein: In formula (I), R1 and R3 are hydrogen; and R2 is at least one selected from hydrogen, amino, hydroxyl, methyl, ethyl and dodecyl.

7. The preparation method according to any one of claims 4 to 6, wherein: The benzenesulfonic acid compound is selected from at least two of p-toluenesulfonic acid, dodecylbenzenesulfonic acid and 4-hydroxybenzenesulfonic acid, preferably a mixture of p-toluenesulfonic acid and dodecylbenzenesulfonic acid, more preferably a molar ratio of toluenesulfonic acid to dodecylbenzenesulfonic acid of 0.5-2:

1.

8. The preparation method according to any one of claims 4 to 7, wherein: In terms of molar ratio, alkaline substances are OH - The zirconium salt is calculated as zirconium, OH-:Zr=2-4.6:1; and / or In terms of molar ratio, template: Zr = 3-40: 100; and / or The concentration of zirconium salt in the zirconium salt aqueous solution is 10-50wt%; and / or In step (2), the mixing temperature is 35-60°C; and / or In step (3), the hydrothermal conditions include: a temperature of 90°C-115°C; and / or a time of 8-72 hours; and / or In step (4), the product obtained in step (3) is cooled to below 35°C; and / or In step (4), the drying conditions include: the drying temperature is 110-120°C.

9. The preparation method according to any one of claims 4 to 8, wherein: In step (1), the alkaline substance is at least one selected from aqueous ammonia, sodium hydroxide, sodium carbonate and ammonium carbonate, preferably aqueous ammonia; and / or In step (2), the zirconium salt is selected from zirconium oxychloride and / or zirconium nitrate; In step (2), the solution obtained in step (1) is dripped into the zirconium salt aqueous solution at a constant flow rate, preferably at a flow rate of 10-100 mL / min; and / or In step (3), a hydrothermal reaction is carried out under constant temperature conditions.

10. Use of the nano zirconium hydroxide according to any one of claims 1 to 3 in a catalyst carrier, preferably in the preparation of an isomerization catalyst.

11. A catalytic method for skeletal isomerization of n-butane, characterized in that: The method comprises: contacting a raw material containing n-butane with a catalyst and H2, wherein the catalyst contains the nano zirconium hydroxide described in any one of claims 1-3.

Citation Information

Patent Citations

  • Method for preparing powder of zirconium oxide in high purity

    CN101049965A

  • Method for preparing zirconium oxide polycrystalline powder with ordered laminar nanostructure / mesoporous structure by using surfactant as template

    CN101913649B

  • Preparation method of zirconium hydroxide

    CN107500351A

  • Production method of zirconium hydroxide

    CN111422904A

  • Method and device for continuous production of nano porous Zr(OH)4 ball by quasi-gaseous state process

    CN101229929A